Antimicrobial coatings prepared from Dhvar-5-click-grafted chitosan powders. (15th January 2019) - Barbosa, Mariana; Costa, Fabíola; Monteiro, Cláudia; Duarte, Filipa; Martins, M. Cristina L.; Gomes, Paula
Graphical abstract: Abstract: Antimicrobial peptides (AMP) are powerful components of the innate immune system, as they display wide activity spectrum and low tendency to induce pathogen resistance. Hence, the development of AMP-based coatings is a very promising strategy to prevent biomaterials-associated infections. This work aims to investigate if Dhvar-5-chitosan conjugates, previously synthesized by us via azide-alkyne "click" reaction, can be applied as antimicrobial coatings. Ultrathin coatings were prepared by spin coater after dissolving Dhvar-5-chitosan conjugate powder in aqueous acetic acid. Peptide orientation and exposure from the surface was confirmed by ellipsometry and contact angle measurements. Bactericidal activity was evaluated against Staphylococcus epidermidis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, the most prevalent pathogens in implant-associated infections. Results showed that Dhvar-5-chitosan coatings displayed bactericidal effect. Moreover, since Dhvar-5 has head-to-tail amphipathicity, it was clear that the bactericidal potency was dependent on which domain of the peptide (cationic or hydrophobic) was exposed. In this context, Dhvar-5 immobilized through its C -terminus (exposing its hydrophobic end) presented higher antimicrobial activity against Gram-positive bacteria and reduced adhesion of Gram-negative bacteria. This orientation-dependent antimicrobial activity was further corroborated by the anti-biofilm assay, as covalent immobilization of Dhvar-5 through its C -terminus provided anti-biofilm properties to the chitosan thin film. Immobilization of Dhvar-5 showed no cytotoxic effect against HFF-1 cells, as both metabolic activity and cell morphology were similar to control. In conclusion, Dhvar-5-chitosan coatings are promising antimicrobial surfaces without cytotoxic effects against human cells. Statement of Significance: AMP-tethering onto ground biomaterial is still a poorly explored strategy in research. In this work, AMP-tethered ground chitosan is used to produce highly antibacterial ultrathin films. Powdered AMP-tethered chitosan appears as an alternative solution for antimicrobial devices production, as it is suitable for large scale production, being easier to handle for fabrication of different coatings and materials with antimicrobial properties and without inducing toxicity.